2016
DOI: 10.1109/tuffc.2016.2547188
|View full text |Cite
|
Sign up to set email alerts
|

AlN/IDT/AlN/Sapphire SAW Heterostructure for High-Temperature Applications

Abstract: Recent studies have evidenced that Pt/AlN/Sapphire surface acoustic wave (SAW) devices are promising for high-temperature high-frequency applications. However, they cannot be used above 700°C in air atmosphere as the Pt interdigital transducers (IDTs) agglomerate and the AlN layer oxidizes in such conditions. In this paper, we explore the possibility to use an AlN protective overlayer to concurrently hinder these phenomena. To do so, AlN/IDT/AlN/Sapphire heterostructures undergo successive annealing steps from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Due to the wurtzite structure and specific polar bonding, aluminium nitride exhibits considerable piezoelectric performance, enabling its application in modern micro‐electro‐mechanical systems (MEMS) . Other physical properties of AlN, such as the wide bandgap (6.2 eV) and high thermal conductivity, make it a promising candidate for optoelectronic devices operating in the deep ultraviolet region and at high temperatures . Combining its unique characteristics, it can surely become an important material in the field of optical MEMS …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the wurtzite structure and specific polar bonding, aluminium nitride exhibits considerable piezoelectric performance, enabling its application in modern micro‐electro‐mechanical systems (MEMS) . Other physical properties of AlN, such as the wide bandgap (6.2 eV) and high thermal conductivity, make it a promising candidate for optoelectronic devices operating in the deep ultraviolet region and at high temperatures . Combining its unique characteristics, it can surely become an important material in the field of optical MEMS …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Other physical properties of AlN, such as the wide bandgap (6.2 eV) and high thermal conductivity, make it a promising candidate for optoelectronic devices operating in the deep ultraviolet region and at high temperatures. [4,5] Combining its unique characteristics, it can surely become an important material in the field of optical MEMS. [6,7] The synthesis of high-quality AlN films in a cost-efficient manner remains a difficult task due to the binary nature of the material as well as the technological demands, such as fast growth rates, technology-compatible substrates, and wafer-scale deposition.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, at least one of the layers has to be a piezoelectric material in order to generate the acoustic waves. One additional advantage of packageless WLAW sensors is that the electrodes are buried and thus protected from physical and chemical alterations [16]. The extreme miniaturization of the device, achieved by removing the package, is also interesting for industrial perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…The ZnO film structure is used to improve the sensitivity of bio-sensors [9] and AlN thin film is used for the high temperature sensor [10]. Further studies have shown that it is possible to produce SAW temperature sensors [11,12] and SAW magnetic sensors [2,13]. Besides being used in SAW devices associated with good piezoelectric coupling, AlN has high acoustic velocity and good thermal and chemical stability.…”
Section: Introductionmentioning
confidence: 99%